Recent Insights Into the Role of Immune Cells in Alcoholic Liver Disease - Li, Sha; Tan, Hor-Yue; Wang, Ning; Feng, Yigang; Wang, Xuanbin; Feng, Yibin (Frontiers in Immunology, 2019)
Accumulating clinical and experimental evidences have demonstrated that both innate and adaptive immunity are involved in the pathogenesis of alcoholic liver disease (ALD), in which the role of immunity is to fuel the inflammation and to drive the progression of ALD. Various immune cells are implicated in the pathogenesis of ALD. The activation of innate immune cells induced by alcohol and adaptive immune response triggered by oxidative modification of hepatic constituents facilitate the persistent hepatic inflammation. Meanwhile, the suppressed antigen-presenting capability of various innate immune cells and impaired function of T cells may consequently lead to an increased risk of infection in the patients with advanced ALD. In this review, we summarized the significant recent findings of immune cells participating in ALD. The pathways and molecules involved in the regulation of specific immune cells, and novel mediators protecting the liver from alcoholic injury via affecting these cells are particularly highlighted. This review aims to update the knowledge about immunity in the pathogenesis of ALD, which may facilitate to enhancement of currently available interventions for ALD treatment.